Transforming the Culinary Arts Curriculum in South Africa: A University Case Study - Fisher, H.; Du Rand, G.; Roets, L.; Makina, A. (South African Journal of Higher Education, 2024)
In South Africa, many graduates cannot secure employment after completing their degree qualification. This is often due to a lack of experience, or curricula not aligned with the needs of employers, current workplaces and the relevant broader industry and society. To address this, curricula must be revised, renewed, or completely transformed. This article focuses on students’ points of view on curriculum transformation; it explores their experiences, opinions, and suggestions to provide insight that will aid in short- or long-term changes to create a responsive and transformed curriculum. Findings from the sample of 19 students at the University of Pretoria in South Africa suggest opportunities to include Afrikan knowledge, innovative culinary practice, and adaptable and flexible delivery methods to improve student engagement and work-integrated learning within the Culinary Arts module. These results show the article’s contribution to ideas and approaches needed to encourage sustainable hospitality and tourism development in the Afrikan region using responsive and transformed curricula. In the future, a student-centred culinary curriculum may produce graduates with fine-tuned abilities, knowledge, and attitudes to address modern-day industry needs, along with a sense of how their contribution could help to address the socio-economic inequalities of South Afrika and Afrika.